NASH EQUILIBRIUM MODEL FOR CONFLICTS IN PROJECT MANAGEMENT - Huynh, Thang Quyet; Trinh, Ngoc Bao; Nguyen, Thang Xuan (Journal of Computer Science and Cybernetics, 2019)
There are many types of concern to project management, we used to deal with them using Risk management activities. But in the complicated situation, there are many factors and preconditions of the issues that make the issues be unrecognizable with risk consultants, and the consequences of these issues getting more and more enormous. The cause of issues can be a conflict between the project teams and their partners or maybe big inside their team, or between teams. These issues called the conflict in a project which never been considered in Risk management. The solution of solving these unseen conflicts can result in cost, schedule, and quality of the project. Good conflict control is a key project management practice to ensure that the least number of surprises occur while your project is underway. In recent research trends, the conflict in some types used to be explained in Game Theory model, and this research aimed to analyze types of conflicts in project management. We proposed a model of conflict in both type having project stakeholders in or not in conflict, later, we defined a Nash Equilibrium model for all type of conflicts which can be used in a multi-objective optimization algorithm then. Finally, we tested this model by building an application of Multi-round procurement problem which is a typical conflict in project management. Based on the result in experiment, the Game-theoretical model of Multi-round procurement was come to usable in finding a solution for the conflict problem. We believe that this research will help in handling another kind of conflicts in project management.